2009
DOI: 10.1177/147323000903700304
|View full text |Cite
|
Sign up to set email alerts
|

Subpopulations of Stem-like Cells in Side Population Cells from the Human Bladder Transitional Cell Cancer Cell Line T24

Abstract: Cancer stem cells can be isolated from human tumours using specific cell surface markers. Bladder cancer cells, however, lack specific cell surface markers, making this approach impracticable. In this study an alternative method was used, involving isolation of side population cells to explore the stem cell characteristics of bladder cancer. Side population cells were isolated from the bladder transitional cell cancer cell line T24 and examined for potential stem cell characteristics related to proliferation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 26 publications
2
36
0
Order By: Relevance
“…Furthermore, expression of the ABC transporters ABCG2 and ABCB1 (also known as MDR1) was confirmed, and side population cells express the stem cell markers POU5F1 and BMI1, implying a stem-like phenotype of side population cells (36). In an independent study, side population cells isolated from the T24 bladder cancer cell line showed a more quiescent cell state, asymmetric cell division, rapid cell growth, and colony formation and chemo-and radioresistance, providing further evidence for CSC enrichment (37). Moreover, side population cells isolated from patient samples have increased clonogenic and proliferative capacity, a higher percentage of quiescent cells, and long-term selfrenewal.…”
Section: Urothelial Stem Cellsmentioning
confidence: 80%
“…Furthermore, expression of the ABC transporters ABCG2 and ABCB1 (also known as MDR1) was confirmed, and side population cells express the stem cell markers POU5F1 and BMI1, implying a stem-like phenotype of side population cells (36). In an independent study, side population cells isolated from the T24 bladder cancer cell line showed a more quiescent cell state, asymmetric cell division, rapid cell growth, and colony formation and chemo-and radioresistance, providing further evidence for CSC enrichment (37). Moreover, side population cells isolated from patient samples have increased clonogenic and proliferative capacity, a higher percentage of quiescent cells, and long-term selfrenewal.…”
Section: Urothelial Stem Cellsmentioning
confidence: 80%
“…Subpopulations of stem-like cells expressing BCRP were found in cell lines or primary tumor samples from a wide assortment of solid tumors, including head and neck cancer [205–207], breast carcinoma [202], small cell and non-small cell lung cancer [208212], gastrointestinal cancers including pancreatic [213, 214], colon [215, 216] and hepatocellular [217219], ovarian cancer [220], gliomas [221, 222], malignant peripheral nerve sheath tumors [223], osteosarcoma [224, 225], prostate cancer [226], Ewing’s sarcoma [227], odontogenic tumors [228], transitional cell carcinoma of the bladder [229], and neuroblastoma [230]. Details of these findings will be discussed within individual tumor types in the ensuing paragraphs.…”
Section: Section 5 Recent Findings In Solid Tumorsmentioning
confidence: 99%
“…In malignant amelioblastic (odontogenic) tumors, CD133, BMI-1 and ABCG2 were found to be expressed; BCRP expression was higher in the neoplastic tissue than in tooth germ tissues [228]. Evidence for SP cells that overexpress BCRP/ABCG2 was found in the bladder transitional cell carcinoma cell line T24 [229]. Evidence for a stem cell population was found in 4 of 8 neuroblastoma cell lines which expressed the stem cell markers CD133, ABCG2 and nestin [230].…”
Section: Section 5 Recent Findings In Solid Tumorsmentioning
confidence: 99%
“…Our results showed that Sal significantly reduced the percentage of CD44 + /CD24 À cell population in a dose dependent manner. Recent studies have shown that high ALDH activity is an additional defining marker of BCSCs [37][38][39][40] and can serve as a useful biomarker for CSCs [25]. Thus, levels of ALDH1 mRNA and protein are relevant in the evaluation of the ability of Sal to specifically target BCSCs.…”
Section: Discussionmentioning
confidence: 99%